1967
DOI: 10.1126/science.158.3807.1471
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Use of a "Fecal Shield" by a Beetle Larva

Abstract: The larva of Cassida rubiginosa carries a tight packet of cast skins and feces on a fork held over its back. The packet is a maneuverable shield used by the larva to protect itself against attack. It is highly effective in blocking the bite of ants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
1
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 1 publication
2
78
1
1
Order By: Relevance
“…The list of enemies potentially deterred by the thatch must extend beyond the coccinellid larva and predaceous pentatomid tested by us. Ants must certainly constitute a hazard and might well be thwarted by the thatch, as they are by the fecal shield of other cassidines (1,5). It is noteworthy that, whereas the Hemisphaerota thatch appears to be pentatomid-proof, the shield of other cassidines offers only limited protection against heteropterans (2).…”
Section: Discussionmentioning
confidence: 99%
“…The list of enemies potentially deterred by the thatch must extend beyond the coccinellid larva and predaceous pentatomid tested by us. Ants must certainly constitute a hazard and might well be thwarted by the thatch, as they are by the fecal shield of other cassidines (1,5). It is noteworthy that, whereas the Hemisphaerota thatch appears to be pentatomid-proof, the shield of other cassidines offers only limited protection against heteropterans (2).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae can carry masses of exuviae and feces that accumulate on a fork-like structure located on the last segment of the abdomen, forming a shield-like structure (Eisner & Eisner, 2000). Previous studies have demonstrated that the shield provides protection against various groups of predators (Eisner et al, 1967;Root & Messina, 1983;Olmstead & Denno, 1993;Vencl et al, 1999;Eisner & Eisner, 2000), but there are also cases in which fecal shields can serve as an attractive cue for generalist predators (Müller & Hilker, 1999). Several authors have shown that the protection is provided by chemical compounds found in the fecal shield (Gómez et al, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…Tortoise beetles that vigorously wave their shields can beat back attacking predators (Eisner et al 1967;Go´mez 1997;Chaboo 2002;Mu¨ller 2002;Nogueira-de-Sa´and Trigo 2002); however, shields appear to be more than simple barriers. Chemical factors contribute to effective shield function in all our study species.…”
Section: Discussionmentioning
confidence: 99%